2015
DOI: 10.1091/mbc.e14-08-1337
|View full text |Cite
|
Sign up to set email alerts
|

c-di-GMP induction ofDictyosteliumcell death requires the polyketide DIF-1

Abstract: Two inducers, DIF-1 and c-di-GMP, each separately shown to play a major role in Dictyostelium cell death induction in vitro, in fact cooperate. A similar cooperation with polyketides might occur for c-di-GMP effects in other situations and organisms, in particular in innate immunity and cell death in animal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Recent studies found strongly reduced c-di-GMP induction of the vacuolated stalk/basal disk cell type in stlb− and dmta− mutants in vitro (12). We show that stalk gene transcription in stlb− and dmta− mutants in vitro required 10-fold higher c-di-GMP concentrations than in wild-type cells (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies found strongly reduced c-di-GMP induction of the vacuolated stalk/basal disk cell type in stlb− and dmta− mutants in vitro (12). We show that stalk gene transcription in stlb− and dmta− mutants in vitro required 10-fold higher c-di-GMP concentrations than in wild-type cells (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…164,165 c-di-GMP is a universal bacterial second messenger 166 and can trigger innate immunity in bacterially-infected animal cells. 167 Unexpectedly, experiments using both inducers show marked synergy, 168 although c-di-GMP alone is insufficient to induce cell death in D. discoideum cell monolayers, requiring either DIF-1 or a DIF-1-related polyketide. The required DIF-1 can be endogenous, as shown by the inability of c-di-GMP to induce cell death when DIF-1 synthesis was blocked pharmacologically (by cerulenin), and by its rescue upon complementation by exogenous DIF-1.…”
Section: Autophagy and Cell Death Pathways In D Discoideummentioning
confidence: 99%
“…). Cells in clumps were also primed to respond to the second exogenous signal (DIF‐1, or as shown more recently c‐di‐GMP ), which led to vacuolization and cellulose encasings . Thus, the latter prominent hallmarks of developmental cell death were induced separately from and after initial cell dysfunction ( Fig.…”
Section: Dictyostelium Cell Death Shows Early Nucleolar Disorganizationmentioning
confidence: 77%